2008
DOI: 10.1016/j.hrthm.2008.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular ectopy during treadmill exercise stress testing in the evaluation of long QT syndrome

Abstract: Background Long QT syndrome (LQTS) can present with sudden death during exertion. Objective To determine the diagnostic importance of exercise-induced ventricular ectopy in the evaluation of LQTS. Methods From 1998 to 2006, 381 patients with a referral diagnosis of LQTS had a treadmill exercise stress test. Blinded to both genotype and rendered diagnosis, the stress tests were scored for the presence of exercise-induced ventricular ectopy. Results The dismissal diagnosis was LQTS in only 177 (46%), catec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 15 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…QRS morphology suggests an outflow tract origin of the initiating beat in more than 50% of patients, and subsequent beats portray a polymorphic or typically bidirectional VT morphology (46). NSVT induced by treadmill exercise testing aimed at evaluating presumed LQTS suggests catecholaminergic polymorphic VT rather than LQTS (47). Beta-blocker therapy is the treatment of choice, probably together with calcium-channel blockers (48).…”
Section: Nsvt In Apparently Normal Heartmentioning
confidence: 99%
“…QRS morphology suggests an outflow tract origin of the initiating beat in more than 50% of patients, and subsequent beats portray a polymorphic or typically bidirectional VT morphology (46). NSVT induced by treadmill exercise testing aimed at evaluating presumed LQTS suggests catecholaminergic polymorphic VT rather than LQTS (47). Beta-blocker therapy is the treatment of choice, probably together with calcium-channel blockers (48).…”
Section: Nsvt In Apparently Normal Heartmentioning
confidence: 99%
“…It has been used as part of the diagnostic evaluation for arrhythmias and arrhythmia disorders such as long QT syndrome, catecholiminergic VT, and frequent ventricular ectopy. [4,8,10] It has also been used to assess the utility of anti-arrhythmic medications in many of these conditions [18]. In addition, recent guidelines published through the Heart Rhythm Society have suggested that an exercise stress test should be considered in the evaluation of young patients greater than 8 years of age with asymptomatic ventricular pre-excitation (WPW) [3].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with or suspected for long QT syndrome (in particular type 1) exercise testing may also trigger ventricular arrhythmias, but ventricular ectopy beyond isolated VPBs is much more common (87.5%) in CPVT patients as compared with long QT syndrome patients (7%). 35 The presence of bigeminy has a specificity of 96% and a sensitivity of 81% for CPVT. 35 Holter monitoring may be used as an alternative test, for instance in children that are too young to undergo exercise testing, or when a patient's symptoms are more emotion-then exercise-related.…”
Section: Clinical Diagnosismentioning
confidence: 99%
“…35 The presence of bigeminy has a specificity of 96% and a sensitivity of 81% for CPVT. 35 Holter monitoring may be used as an alternative test, for instance in children that are too young to undergo exercise testing, or when a patient's symptoms are more emotion-then exercise-related. Finally, catecholamine infusion may be used to unmask CPVT.…”
Section: Clinical Diagnosismentioning
confidence: 99%